Haematological characteristics of the beta 0 thalassaemia trait in Sardinian children. Issue 10 (October 1980) - Galanello, R; De Virgiliis, S; Addis, M; Paglietti, E; Ruggeri, R; Cao, A
Abstract : We report red cell indices and haemoglobin (Hb)A2 levels in Sardinian children with heterozygous beta 0-thalassaemia and in normal controls aged 6 months to 12 years. Iron-deficient children and those with haematological findings indicative of alpha-thalassaemia were excluded. As in adult carriers, these subjects have significantly increased mean red cell counts and significantly reduced mean Hb levels, mean corpuscular volume (MCV), mean corpuscular haemoglobin (MCH), haematocrit, and mean corpuscular haemoglobin concentration. From 66 to 76% of the heterozygous beta 0 thalassaemia children examined were anaemic. MCH and MCV were within the normal range in 2.8% of these children. Serum ferritin levels showed no difference from those of normal controls.